Safety of MRI with Retained Civilian Bullets. (16th November 2020) - Morrow, Kevin D; Shields, Jessica; Podet, Adam; Park, Joe; Girolamo, Taylor W; Wilson, Jason D; DiGiorgio, Anthony M
Abstract: INTRODUCTION: There is a concern for ballistic movement and radiofrequency induced heating causing damage to surrounding structures for patients who undergo MRIs with retained civilian bullets. METHODS: The prospectively maintained trauma database was queried for gun-shot wounds from 2016–2019. Charts from patients with retained bullets who subsequently underwent MRI were reviewed. RESULTS: 1, 977 patients were evaluated for gun-shot wounds. 63 had retained bullets who subsequently underwent an MRI. A total of 67 MRIs were completed. 35 of the MRIs were performed within one month of the injury. 36 of the MRI images involved the same body part of the retained bullet. The majority of retained bullets were either near-complete projectile, fragmentation, or a combination of the two. 2 patients had retained intracranial bullets that underwent MRI Brain. 5 patients had retained intraspinal bullets/fragments that underwent an MRI spine. Following completion of MRIs, 17 patients had follow-up CTs that included imaging of the retained bullets. 11 of these 17 were performed within 1 month of the MRI. 3 bullets showed rotational movement; 1 bullet showed translational movement of .9 cm inferior. 13 patients did not have CT following the MRI but did have post-MRIs X-rays involving the retained bullet. There was no obvious bullet migration on these radiographs. There were no reported immediate complications as the result of an MRI. CONCLUSION: MRIs with retained civilian non-ferromagnetic ballistics produced in the United States are generally safe but each MRI should be completed on a case to case basis. Due to evidence of both rotational and translational movement, one should avoid MRIs for retained bullets near nerves or major blood vessels. There were no reported complications from undergoing MRI with retained projectiles.